2020
DOI: 10.3390/medicina56120718
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Maximal Strength Training on Perceived-Fatigue and Functional Mobility in Persons with Relapsing-Remitting Multiple Sclerosis

Abstract: Background and objectives: Fatigue is one of the most disabling symptoms that limit daily life activities in persons with multiple sclerosis (pwMS). This study aimed to evaluate the effects of maximal strength training (MST) on perceived-fatigue and functional mobility in pwMS. Materials and Methods: 26 participants with MS were balanced according to their pre-intervention fatigue scores and distributed into an MST group (n = 13) and a control group (CG; n = 13). The MST group completed eight weeks using high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…While only three trials presented as low risk 77 , 83 , 98 . In the domain of missing outcome data, 22 trials presented a low risk of bias 37 , 61 , 68 , 70 , 72 , 74 , 76 , 79 81 , 83 86 , 90 , 91 , 93 , 95 – 99 while only four presented a high risk of bias 62 , 64 , 78 , 88 . 15 trials showed a low risk of bias 61 , 70 72 , 78 , 79 , 83 , 86 , 87 , 90 , 91 , 93 , 95 97 in the measurement of outcome domain while three showed a high risk of bias 73 , 74 , 88 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While only three trials presented as low risk 77 , 83 , 98 . In the domain of missing outcome data, 22 trials presented a low risk of bias 37 , 61 , 68 , 70 , 72 , 74 , 76 , 79 81 , 83 86 , 90 , 91 , 93 , 95 – 99 while only four presented a high risk of bias 62 , 64 , 78 , 88 . 15 trials showed a low risk of bias 61 , 70 72 , 78 , 79 , 83 , 86 , 87 , 90 , 91 , 93 , 95 97 in the measurement of outcome domain while three showed a high risk of bias 73 , 74 , 88 .…”
Section: Resultsmentioning
confidence: 99%
“…In the domain of missing outcome data, 22 trials presented a low risk of bias 37 , 61 , 68 , 70 , 72 , 74 , 76 , 79 81 , 83 86 , 90 , 91 , 93 , 95 – 99 while only four presented a high risk of bias 62 , 64 , 78 , 88 . 15 trials showed a low risk of bias 61 , 70 72 , 78 , 79 , 83 , 86 , 87 , 90 , 91 , 93 , 95 97 in the measurement of outcome domain while three showed a high risk of bias 73 , 74 , 88 . Ten trials presented a low risk of bias 61 , 72 , 86 , 87 , 91 , 93 , 95 97 , 117 in the selection of reported results while no trials presented a high risk.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding fatigue and its influence on the frailty of the population under consideration, previous studies have demonstrated the efficacy of resistance exercise as a mitigating factor for this effect [ 60 ]. Additionally, noteworthy is the impact that the combination of resistance training with motor control training can have on fatigue, leading to significant improvements in fatigue levels [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Irrespective of cause, PNP often results in considerable functional impairments, i.e., increased tendency to fall, dependency on walking aids, inability to ascend-descend stairs and difficulties in activities of daily living ( Callaghan et al, 2015 ; Hoffman et al, 2015 ). Strength training has been shown to improve strength, gait and functional outcomes in healthy young and older adults ( de Vos et al, 2005 ; Liu and Latham, 2009 ; Garber et al, 2011 ; Raymond et al, 2013 ; Borde et al, 2015 ; Hvid et al, 2016 ; Chen et al, 2021 ), patients with stroke ( Hill et al, 2012 ) and patients with multiple sclerosis ( Dalgas et al, 2009 ; Gomez-Illan et al, 2020 ). Since treatment only exists for very few percentages of the potential underlying causes (inflammatory) it is obvious to consider if strength training could be a potential treatment to counteract functional impairments and loss of physical capacity in patients with PNP.…”
Section: Introductionmentioning
confidence: 99%